Self‐sampling as the principal modality for population based cervical screening: Five‐year follow‐up of the PaVDaG study. Issue 8 (6th December 2021) - Stanczuk, Grazyna A.; Currie, Heather; Forson, William; Baxter, Gwendoline; Lawrence, James; Wilson, Allan; Palmer, Timothy; Arbyn, Marc; Cuschieri, Kate
Abstract: Self‐sampling provides a powerful means to engage women in cervical screening. In the original Papillomavirus Dumfries and Galloway study (PaVDaG), we demonstrated cross‐sectional similarity of high‐risk human papillomavirus (Hr‐HPV) testing on self‐taken vaginal vs clinician‐taken samples for the detection of cervical intraepithelial neoplasia 2 or worse (CIN2+). Few data exist on the longitudinal performance of self‐sampling; we present longitudinal outcomes of PaVDaG. Routinely screened women provided a self‐taken and a clinician‐collected sample. Ninety‐one percent of 5136 women from the original cohort completed a further screening round. Sensitivity, specificity, positive predictive value and complement of the negative predictive value of the Hr‐HPV test on self‐samples for detection of CIN2+ and CIN3+ up‐to 5 years after testing were determined. Additionally, clinical accuracy of Hr‐HPV testing on vaginal and clinician‐collected samples was assessed. A total of 183 CIN2+ and 102 CIN3+ lesions were diagnosed during follow‐up. Risk of CIN2+ and CIN3+ following an Hr‐HPV negative self‐sample was 0.6% and 0.2%, respectively, for up to 5 years after testing. The relative sensitivity for CIN3+ and specificity for ≤CIN1 of Hr‐HPV testing on self‐taken specimens was slightly lower vs clinician‐collected samples: 0.95 (95% CI: 0.90‐0.99; P McN = .0625) and 0.98 (95% CI: 0.95‐1.00; P McN = <.0000), respectively. The low risk of CIN2+ in women with Hr‐HPV—self‐sample(s) suggests, that the 3 to 5‐year recall interval implemented in several cervical screening settings, based on clinician‐taken samples, may be safe for self‐samples. Future assessment will show if "universal" 5‐year screening is appropriate for programs based on self‐sampling. Abstract : What's new? Primary screening for high‐risk human papillomavirus (Hr‐HPV) provides better protection against cervical cancer than cytology‐based cervical screening. While Hr‐HPV‐based screening programmes create an opportunity for vaginal self‐sampling, the longitudinal performance of self‐sampling remains to be determined. Here, the authors provide one of the first datasets to describe the longitudinal performance of Hr‐HPV testing with self‐taken samples in women who attend population‐based cervical screening. The low risk of high‐grade disease in women with Hr‐HPV‐negative self‐samples suggests that the three‐to‐five‐year recall interval already implemented in cervical screening programmes based on clinician‐taken samples may be appropriate for programmes based on self‐sampling.